Computer Skills and Electronic Health Records (EHRs) in a State Tertiary Hospital in Southwest Nigeria - Maureen Nokuthula Sibiya; Oluwatoyin Rhoda Akinyemi; Olanrewaju Oladimeji (MDPI AG, 2023)
Adopting change is something that is often resisted, as is often the case in the adoption of electronic health records (EHRs) in healthcare organizations. Embracing this will require computer knowledge to handle the system for the management of patients and their care. This study aims to determine the computer skills required for the uptake of electronic health records (EHR) by healthcare workers in an annex of the state teaching hospital, Okela Health Centre (OHC) Ado-Ekiti. The study uses a cross-sectional research design with a structured questionnaire distributed to 30 healthcare workers across seven disciplines working in the hospital. Descriptive statistics of frequency tables and percentages were used to ascertain the relationship between computer skill usage and the adoption of EHR. The majority of respondents were only efficient in Microsoft Word (MW), email, and WhatsApp, with efficiency rates of 63.4%, 76.6%, and 73.3%, respectively. The majority were not efficient in Microsoft Excel (ME) and Microsoft Access (MA), at 56.7% and 70%, respectively. Computer appreciation is an important basis for the adoption of EHR in hospitals.